Effect of seasonal exposure in aeroallergen-sensitised patients with irritable bowel syndrome-diarrhoea - Carlo Maria Rossi; Carlo Maria Rossi; Marco Vincenzo Lenti; Marco Vincenzo Lenti; Stefania Merli; Martina Fiorita; Martina Fiorita; Antonio Lo Bello; Antonio Lo Bello; Mario Andrea Latorre; Mario Andrea Latorre; Paola Ilaria Bianchi; et al. (Frontiers in Allergy)
BackgroundPollen allergy may influence irritable bowel syndrome (IBS) symptoms; however, available data are scant.AimsThis study aims to assess symptom variability in atopic IBS patients.MethodsWe retrospectively analysed consecutive adult IBS patients evaluated between 2021 and 2024. Patients from the overall IBS cohort and the IBS-diarrhoea (IBS-D) subgroup were classified according to their sensitisation into grass-positive, house dust mite (HDM)-positive, or unsensitised. Symptom burden was assessed using the gastrointestinal symptom rating scale (GSRS) and a visual analogue scale for abdominal pain/distension, both outside the season period (T0) and during the pollination season (T1).ResultsA total of 61 IBS patients were recruited (median age 34 years, IQR 25–50, F:M ratio 3.6:1), including 38 patients (62.8%) with IBS-D (median age 30 years, IQR 28–47, F:M ratio 2.8:1). Atopy was common in the IBS-D subgroup, particularly with respiratory manifestations. The mean GSRS significantly (p < 0.01) increased at T1 (variance of 3.4 points) only in grass-sensitised patients as opposed to those sensitised to HDM or unsensitised ones; this effect was present only in the IBS-D subgroup, while no significant variation was observed in the overall cohort.ConclusionsPollination season influences symptoms in IBS-D patients sensitised to seasonal allergens.